Investigating low adaptive behaviour and presence of the triad of impairments characteristic of autistic spectrum disorder as indicators of risk for challenging behaviour among adults with intellectual disabilities. (1st February 2012) - Felce, D.; Kerr, M.
Abstract Background Identification of possible personal indicators of risk for challenging behaviour has generally been through association in cross‐sectional prevalence studies, but few analyses have controlled for intercorrelation between potential risk factors. The aim was to investigate the extent to which gender, age, presence of the triad of impairments characteristic of autism and level of adaptive behaviour were independently associated with level of challenging behaviour among adults with intellectual disabilities. Methods Five datasets were merged to produce information on challenging behaviour, adaptive behaviour, presence of the triad of impairments, gender and age of 818 adults. Variables were entered into a multivariate linear regression, which also tested the interaction between the presence of the triad of impairments and level of adaptive behaviour. Results Presence of the triad of impairments, level of adaptive behaviour, their interaction, and age, but not gender, significantly and independently contributed to the prediction of challenging behaviour. Presence/absence of the triad of impairments moderated the effect of adaptive behaviour on challenging behaviour. The inverse relationship found in the absence of the triad of impairments was virtually removed when present. Conclusions This study has shown that it is necessary to control for intercorrelation between potential risk factors for challenging behaviour and to explore how interaction between them might moderate associations.